Polanyi and the Instituted Processes of Markets: Introducing a Wellbeing Perspective - Johnson, Susan (2009)
Analysis of the role of markets in development is mainly focused on their ability to promote material provisioning. Polanyi argued that markets were only one approach to material provisioning, and that the concept of the self-regulating market had become disembedded from society. He was concerned that processes of provisioning be understood within the wider framework of society and developed the concept of instituted process as a means to understand this role. This paper sets out to explore whether and how Polanyi’s concept of instituted process might work with emerging approaches to analysing wellbeing – what it means to live well – to offer tools for the institutional analysis of markets.
Keywords: embeddedness; instituted economic process; instituted process; institutions; well-being

Politics, the state and the impulse for social protection : the implications of Karl Polanyi's ideas for understanding development and crisis - Putzel, James (London School of Economics Crisis States Research Centre working papers series 1, 18., 2002)
This short paper discusses how some of Karl Polanyi's key ideas can help shed light on the processes of development and crisis in the world today. It begins by taking up the role of economic liberalisation and the state. Then it discusses Polanyi's identification of the 'impulse' for 'social protection' and suggests it is crucial to an understanding not only of the role of the state in development but also politics in the developing world. It finishes by applying some of these ideas to understanding the actions of 11th September, and the crisis related to terrorism in the developing world today.
Keywords: development; economic theory; political institutions; social history; social problems; social protection; social reform